Age-related changes in vascular responses to angiotensin-(1-7) in female mice. (July 2018) - Costa-Fraga, Fabiana P; Goncalves, Gleisy K; Souza-Neto, Fernando P; Reis, Adelina M; Capettini, Luciano AS; Santos, Robson AS; Fraga-Silva, Rodrigo A; Stergiopulos, Nikolaos; da Silva, Rafaela F
The vasodilatory effect of angiotensin-(1-7) seems to vary between sexes, and estradiol (E2) can modulate the magnitude of the Ang-(1-7) vasodilatory response in female rats. However, there are few studies addressing the influence of sex on the age-related vasodilatory effect of Ang-(1-7). Here, we evaluated the vasodilatory response to Ang-(1-7) on vascular ageing. Ang-(1-7) dose–response curves were determined in mice aortic rings from males (old and young) and females (E2 treated/non-treated old and young) mounted in an isolated organ chamber. Abdominal aortic rings were used for protein expression analysis and determination of reactive oxygen species (ROS) and nitric oxide (NO) production. Our results showed that the Ang-(1-7) vasodilatory effect was absent in aorta from old females, contrasting with a full response in vessels from young females. The Ang-(1-7) vasodilatory effect was restored by E2 replacement in old females. A robust increase in Mas receptor, SOD2, NRF-2 and NOX2 expression was observed in aorta from old females, which was normalized by E2. This effect of E2 was also associated with lower production of ROS and normal levels of NO. In conclusion, our data demonstrated that pathways involved in the Ang-(1-7) vasodilatory response in female mice is affected by hormonal changes in ageing and rescued by E2.